PERBANDINGAN KOMPONEN MINYAK ATSIRI ANTARA DAUN MUDA DAN DAUN DEWASA PADA HYPTIS SUAVEOLENS (L.)POIT - Moralita Chatri; Mansyurdin Mansyurdin; Amri Bakhtiar; Perri Adnadi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Hyptis suaveolens (L.) Poit is one of the species Lamiaceae family (Labiatae), is an aromatic plant and can produce essential oils. Essential oils of these plants can be utilized as antimicrobials. The chemical components contained in the essential oils in the same plant may vary as they are influenced by several factors, including the growth stage. Essential oils can be obtained by hydrodestilation and their components are analyzed using gas chromatography-mass spectrometry (GC-MS). The essential oil components are then compared between those found in young leaves and adult leaves. The results of analysis and identification showed that in young leaves there are 50 components while in adult leaves there are only 37 components. The main components of young leaves were ?-caryophyllene (34.65%), germacrene-D (10.32%), ?-bergamotene (6.56%), ?-copaene (5.94%) and rimuene (6.46%), Are ?-caryophyllene (23.53%), germacrene-D (9.52%), ?-elemente (6.53%) and rimuene (13.19%). The components of ?-bergamotene and ?-copaene are not found in adult leaves.